Effect Of Topical Tinospora Cordifolia On Healing Of Burn Wounds In Wistar Rats - GIRISH MERAVANIGE,; KAMDOD M A, (International Journal of Pharma and Bio Sciences, 2012)
Objective: To investigate the effect of tinospora cordifolia (TC) on the healing of burn wounds in wistar rats and compare it with control and silver sulfadiazine treated groups. Materials and Methods: Partial thickness burn wounds were made on three groups of rats (n=6 in each group) at the nape of neck under ether anesthesia. The Burn wounds were treated topically with petroleum base, 1% silver sulfadiazine and 2% TC, respectively once daily till complete healing. The wound contraction rate and epithelialization time were observed. Data was analysed by one way ANOVA and Tukeys multiple post hoc procedures. Results: The mean epithelialization time was significantly (P<0.0004*) decreased in TC treated group compared to control and silver sulfadiazine groups. Percentage of wound contraction was significantly more on 4th (P<0.0003*), 8th (P<0.0019*), 12th (P<0.0060*) and 16th day (P<0.0016*) in TC treated group in comparison to the control. Conclusion: Topical TC showed healing potential on burn wounds in wistar rats.